Dieta e estrutura da rede trófica de morcegos em áreas verdes urbanas em Sergipe - Malaquias, Ellen da Costa (2021)
The diversity of morphological and behavioral characteristics of bats reflects the variety of feeding habits and the roles they play in communities. Seasonality, different energy requirements, and urbanization can affect bats' diets. Factors such as structural change in habitat, increased exposure to predators, and noise and visual pollution affect behavior and foraging in these environments, altering local trophic networks. The objectives of this dissertation were (1) to analyze the diet and the influence of sex and precipitation on the consumption of food items; (2) to characterize the structure of the bats' trophic network. Bats were captured in mist nets between September/2019 and August/2020 in three urban green areas of the metropolitan region of Aracaju, Sergipe. The food items consumed were identified by analyzing the feces obtained in the field. The first chapter characterizes the composition of the diet of each species, the influence of sex and rainfall on this diet (G-test and simple logistic regression, respectively) and the trophic niche. There was predominance in the consumption of fruits of common species of the pioneer stages of succession, which is related to the state of conservation of urban environments. The genus-genus relationship was identified, with Artibeus spp. and Platyrrhinus lineatus frequently consuming Cecropia spp., Carollia perspicillata feeding on Piper spp. and Sturnira lilium from Solanum spp. The diet was influenced by sex in the most frequent species due to nutritional and energy needs. In general, precipitation did not influence the composition of the species' diet, with the exception of P. lineatus in relation to the consumption of Cecropia pachystachya. Artibeus lituratus had a wider niche range (B=5.53), with greater overlap with A. planirostris (Øjk = 0.88) and P. lineatus (Øjk = 0.72). In the second chapter, the trophic network structure of the general community was analyzed and the robustness of the network to the extinction of the species was evaluated. The trophic bat network found in urban green areas exhibited low nesting structure (greater participation of generalist species) and greater modularity, due to the preferences of certain bat species to some food items (frugivores). A low connectivity and intermediate specialization reflect those bats had interactions with few food items. The species with the highest connectivity (A. lituratus) explored only half of the items registered in the network, usually the most frequent in urban green areas. Trophic network has been shown to be more sensitive to the loss of generalist species, as they are the species with the greatest variety of connections and that give the network greater stability.